Strategi dalam Meningkatkan Kerja Sama Tim di Lingkungan Kerja - Nurun Nisaul Khusna; Haya Fatimah; Sri Oktavianah; Efnita Mayang Sari (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2026)
Teamwork is a fundamental factor in social, organizational, and educational life, because in essence humans are social creatures that require the interaction and involvement of other individuals to meet their needs and achieve life goals. In the context of work, teamwork can be defined as the result of coordinated individual efforts that are able to produce higher performance than if work is done individually, or as a group of individuals working collectively to achieve common goals that are easier to achieve through collaboration. The implementation of teamwork plays an important role in accelerating job completion, improving individual and organizational performance, and being able to prevent overlapping tasks through good synchronization. Through intensive interaction, teamwork can have a positive impact on the overall performance of the group and also improve individual abilities through the process of knowledge and experience transfer between employees. The dimension of teamwork includes active member contributions, interaction and communication, consistency in maintaining focus on goals, quality of work results, and relevance of team members' knowledge and skills. Therefore, the effectiveness of teamwork is seen as the most important competitive advantage in an organization, making it a major factor that influences the increase in work productivity.